Developing methods to compare tablet formulations of atorvastatin (Brazilian Journal of Pharmaceutical Sciences, 2012)
Atorvastatin (ATV) is an antilipemic drug of great interest to the pharmaceutical industry. ATV does not appear in the monographs of Brazilian pharmacopoeia, and analytical methodologies for its determination have been validated. The chromatographic conditions used included: RP-18 column-octadecylsilane (250 x 4.6 mm, 5 mm), detection at 238 nm, mobile phase containing 0.1% phosphoric acid and acetonitrile (35:65% v/v), flow at 1.5 mL min-1, oven temperature at 30ºC, and injection volume of 10 mL. ATV is classified as a class II product, according to the biopharmaceutical classification system. As such, a dissolution test was proposed to evaluate pharmaceutical formulations on the market today, under the following conditions: water as a dissolution medium, 1000 mL as a volume, paddle apparatus at a rotation speed of 50 rpm, 80% (Q) in 15 minutes with UV spectrophotometer readings at 238 nm. In the pattern condition proposed as the ideal dissolution test, which appropriately differentiates amongst formulations, the generic product was not considered pharmaceutically equivalent; however, in other less differential dissolution methods, which also fall within appropriate legal parameters, this product could come to be regarded as generic.